2013
DOI: 10.1002/erv.2216
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to Visual Food Cues: Insights from Functional Magnetic Resonance Imaging

Abstract: The aim of this paper is to describe the patterns of functional magnetic resonance imaging activation produced by visual food stimuli in healthy participants, as well as in those with anorexia nervosa, bulimia nervosa, binge eating disorder and obesity. We conducted a systematic review of studies published in the last decade on normal and abnormal eating. This review suggested the existence of neural differences in response to the sight of food between healthy individuals, those with an eating disorder and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 121 publications
(235 reference statements)
12
114
3
1
Order By: Relevance
“…The fasted or "hungry" state was associated with increased resting-state regional cerebral blood flow and increased activity in response to visual food cues in the insular cortex (Hinton et al 2004;Chechlacz et al 2009). Recent reviews also have described reduced activation in the insular cortex in those who are obese or overweight, suggesting weakened attempts to control one's appetite (Brooks et al 2013;Garcia-Garcia et al 2013). Given the importance of regulating eating behavior, cortical atrophy in this area may diminish its capacity to receive information on changes in energy balance after food consumption, and this limitation may then lead to excessive food intake.…”
Section: Discussionmentioning
confidence: 93%
“…The fasted or "hungry" state was associated with increased resting-state regional cerebral blood flow and increased activity in response to visual food cues in the insular cortex (Hinton et al 2004;Chechlacz et al 2009). Recent reviews also have described reduced activation in the insular cortex in those who are obese or overweight, suggesting weakened attempts to control one's appetite (Brooks et al 2013;Garcia-Garcia et al 2013). Given the importance of regulating eating behavior, cortical atrophy in this area may diminish its capacity to receive information on changes in energy balance after food consumption, and this limitation may then lead to excessive food intake.…”
Section: Discussionmentioning
confidence: 93%
“…This may be in part due to the fact that previous studies either used a passive delivery of food reward (for an overview, please see ref. 41) or performed a comparison between different stimuli types or different levels of reward during hunger (43), which in effect normalizes the observed signal, so that a general reward level-independent increase in reward processing cannot be assessed. Furthermore, most previous studies were unable to directly compare reward modalities due to differences in task design (for example, Dean and colleagues, ref.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…In the study of Hare and colleagues (2009), the success of self-control on dietary choices (meaning that study participants successfully considered the health aspects of food in their dietary choices) was positively associated with the activity in the dlPFC, subsequently influencing food value attribution as reflected by vmPFC modulations. Other neuroimaging studies have further shown that the brain tracks the energy content of foods (García-García et al, 2013;Killgore et al, 2003; Van der Laan et al, 2011). Responses to varying food types (Toepel et al, 2009) and food portion sizes (Toepel et al, 2015) have been shown to differ already within 200ms after image exposure; reflected by activity modulations in temporo-occipital and frontal brain regions (e.g.…”
Section: Introductionmentioning
confidence: 99%